Faktor-Faktor yang Mempengaruhi Kejadian Demam Berdarah Dengue di Kota Ambon - Suryanti Tukiman; Ratna Sari Rumakey (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Dengue hemorrhagic fever is one of the most common tropical diseases affecting humans, which has become an international disease in recent decades. This study aimed to determine the factors that influence the incidence of dengue hemorrhagic fever in Ambon City. This research was an observational study with a cross-sectional design. The research was conducted in Ambon City from May to June 2022. This research involved 136 respondents who were determined using a total sampling technique. Data was collected by filling out a questionnaire, then analyzed descriptively in the form of frequencies and proportions, then continued with hypothesis testing using the Chi-square test. The results of the analysis showed the p-value for each factor of the incidence of dengue hemorrhagic fever, namely: knowledge = 0.021, habit of hanging clothes = 0.018, frequency of draining water reservoirs = 0.037, availability of water reservoir covers = 0.234 and house density = 0.562. It was concluded that the factors influencing the incidence of dengue hemorrhagic fever in Ambon City were lack of knowledge, the habit of hanging clothes and the lack of frequency of draining water reservoirs. It is hoped that the public will be more active in hygiene measures to avoid dengue hemorrhagic fever.Keywords: dengue hemorrhagic fever; knowledge; hanging clothes; draining water reservoirs ABSTRAK Demam berdarah dengue adalah salah satu penyakit tropis yang paling umum mempengaruhi manusia, yang telah menjadi penyakit berskala internasional dalam beberapa dekade terakhir. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang mempengaruhi kejadian demam berdarah dengue di Kota Ambon. Penelitian ini merupakan studi observasional dengan rancangan cross-sectional. Penelitian dilakukan di Kota Ambon pada bulan Mei sampai Juni 2022. Penelitian ini melibatkan 136 responden yang ditentukan dengan teknik total sampling. Data dikumpulkan melalui pengisian kuesioner, selanjutnya dianalisis secara deskriptif berupa frekuensi dan proporsi, lalu dilanjutkan pengujian hipotesis menggunakan uji Chi-square. Hasil analisis menunjukkan nilai p untuk masing-masing faktor dari kejadian demam berdarah dengue yaitu: pengetahuan = 0,021, kebiasaan menggantung pakaian = 0,018, frekuensi pengurasan tempat penampungan air = 0,037, ketersediaan tutup tempat penampungan air = 0,234 dan kepadatan rumah = 0,562. Disimpulkan bahwa faktor yang mempengaruhi kejadian demam berdarah dengue di Kota Ambon adalah kurangnya pengetahuan, kebiasaan menggantung pakaian dan kurangnya frekuensi pengurasan tempat penampungan air. Diharapkan agar masyarakat agar lebih giat dalam tindakan kebersihan agar terhindar dari demam berdarah dengue.Kata kunci: demam berdarah dengue; pengetahuan; menggantung pakaian; pengurasan tempat penampungan air